PERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS IV SD NEGERI DULOLONG BARAT KECAMATAN ALOR BARAT LAUT KABUPATEN ALORPERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS IV SD NEGERI DULOLONG BARAT KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - abdilah dopu; Yakin AKbar Asikin; Sudarto Lukman Lema (STKIP Muhammadiyah Kalabahi, 2026)
This study aims to (1) determine the role of teachers in developing fourth-grade students at Dulolong Barat Public Elementary School, Alor Barat Laut District, Alor Regency, and (2) determine the obstacles faced by teachers in developing fourth-grade students at Dulolong Barat Public Elementary School, Alor Barat Laut District, Alor Regency. The method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers act as role models, guides, facilitators, and controllers in shaping students' character, especially the values of discipline, responsibility, honesty, and cooperation. Character formation efforts are carried out through positive habits, role models, and reinforcement of values in the learning process. However, teachers also face obstacles such as students' unsupportive family backgrounds and limited time. In conclusion, the role of teachers is very important in developing students' character, and requires support from parents and the surrounding environment.